(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The importance of the science of information technology in education is very great, and it consists of laws and decrees on the process of informatization of education, the use of advanced pedagogical technologies in the teaching of science, the formation of information culture of students studying in all areas of education, and the establishment of a new qualitative stage of the use of information and educational technologies.